Comparative analysis of the main disasters that occurred in the years 1988 to 2022 related to mass landslides in the municipality of Petrópolis in Rio de Janeiro, considering human, physical and environmental aspects - Vianna, Luiz Emílo; dos Santos, Alexandre Luís Belchior; dos Santos, Angélica Pires Belchior (Seven Editora, 2024)
This article was prepared from the master’s thesis in civil protection and defense of the Fluminense Federal University, involving the context of mass landslide disasters in the municipality of Petrópolis, in the Mountain Region of the state of Rio de Janeiro. The period under analysis of the events was the one constant from the years 1988 to 2022. A comparative analysis was carried out between indicators and relevant points of human, physical and environmental aspects among the main disasters of the period. Then, the recurrence and common points of landslide disasters in the municipality were identified to improve the efficiency of mitigating measures and assist civil defense managers in their actions. Information was also gathered that characterizes the geological formation, topography, climate and meteorological conditions, natural conditions that make the municipality vulnerable to disasters involving landslides. The study allowed preliminary results to be reached that point to a cycle of disasters, comprised in the rainiest period in the municipality, with high rainfall. The neighborhoods of Quitandinha and Morin were identified with the highest recurrence of landslides and the climatic and geophysical vulnerability faced by the municipality. In the work, the term mega-disaster was also characterized. DOI:https://doi.org/10.56238/sevened2024.018-055